2014
DOI: 10.1039/c3cp54427c
|View full text |Cite
|
Sign up to set email alerts
|

Predicted disorder-to-order transition mutations in IκBα disrupt function

Abstract: IκBα inhibits the transcription factor, NFκB, by forming a very tightly bound complex in which the ankyrin repeat domain (ARD) of IκBα interacts primarily with the dimerization domain of NFκB. The first four ankyrin repeats (ARs) of the IκBα ARD are well-folded, but the AR5-6 region is intrinsically disordered according to amide H/D exchange and protein folding/unfolding experiments. We previously showed that mutations towards the consensus sequence for stable ankyrin repeats resulted in a “prefolded” mutant. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 23 publications
2
24
0
Order By: Relevance
“…Human IκBα 67-287 (IκBα) mutants were produced using site-directed mutagenesis, and the proteins were expressed and purified as described (30 (31). Murine N-terminal hexahistidine-RelA 19-321 /p50 39-350 heterodimer (NFκB) was coexpressed as described previously (20) and was purified by nickel affinity chromatography, cation exchange chromatography (Mono S; GE Healthcare), and size-exclusion chromatography (Superdex 200; GE Healthcare).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Human IκBα 67-287 (IκBα) mutants were produced using site-directed mutagenesis, and the proteins were expressed and purified as described (30 (31). Murine N-terminal hexahistidine-RelA 19-321 /p50 39-350 heterodimer (NFκB) was coexpressed as described previously (20) and was purified by nickel affinity chromatography, cation exchange chromatography (Mono S; GE Healthcare), and size-exclusion chromatography (Superdex 200; GE Healthcare).…”
Section: Methodsmentioning
confidence: 99%
“…Sensorgrams were recorded on a GE Biacore 3000 instrument using streptavidin chips (GE Healthcare) by immobilizing 150, 250, and 350 response units of p50 dd /biotin-RelA dd on flow cells 2, 3, and 4, respectively, leaving flow cell 1 unmodified for reference subtraction. NFκB-binding experiments were conducted on IκBα(WT) and IκBα(5xPEST), and the data were analyzed as described (18,30).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We observe that in both the cases, the designed proteins and the Toll-like receptor 3, the regions where the wedges are located have a higher proportion of highly frustrated interactions. We have shown for the ANK protein family, that insertions within and in between adjacent repeats are enriched in this type of energetic conflicts [26], most likely because of functional constraints like surface adaptation to bind the target, as suggested in the case of LRRs or for dynamic and regulatory reasons like in the IκBα case [29,33].…”
Section: Repeat Proteins Design: Regular and Highly Stable Moleculesmentioning
confidence: 99%
“…Dembinski et al investigated mutations that promote disorder-to-order transitions in IkBa and showed that these mutations decreased the efficiency of IkBa in inhibiting NFkB. 39 Regulation is a key function of IDPRs. JaramilloTatis et al developed a new SUMO-expression and purification protocol for the preparation of a full length murine SCP1/GIP, and were able to observe the interaction between murine SCP1/GIP and the intrinsically disordered BG21.…”
Section: Analyzing Functions Of Idps and Idprsmentioning
confidence: 99%